Reciprocity in locating contributions: Experiments on the neighborhood public good game - Siegfried Berninghaus; Werner Güth; Stephan Schosser (Games, 2013)
In repeated public good experiments, reciprocity helps to sustain high levels of cooperation. Can this be achieved by location choices in addition to making contributions? It is more realistic to rely on an intuitive neighborhood model for community members who interact repeatedly. In our experiments, participants can locate their contribution, yielding a small benefit for the participant, who receives the contribution and a small disadvantage for the participant, at the opposite location. This mechanism of individually targeted sanctions helps to foster initial cooperation. It decreases over time, however. Location choices are used to reciprocate, but may not suffice to stabilize voluntary cooperation as an effect observed in the field.
Keywords: 330; public good game; neighborhood; cooperation; experimental analysis